2019
DOI: 10.1186/s40780-019-0151-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors that cause insulin precipitation and/or amyloid formation in insulin formulations

Abstract: BackgroundMultiple daily subcutaneous injections (MDSIs) are mainly used for formulating an insulin therapy for diabetic patients; however, they also cause insulin-derived amyloidosis (IDA) and lead to poor glycemic control. In addition, for the continuous subcutaneous insulin infusion system (CSII), precipitation frequently causes catheter occlusion and, if the precipitate in the formulations is amyloid, the injection of the insoluble amyloid into the subcutaneous tissue leads to IDA. The aim of this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…tubing set, the maximum dwell time would be up to 4 h from insulin reservoir to delivery . Previous studies in vitro have not shown fibrillation or degradation occurring at 4 h. ,,, However, it remains to be determined how exposure to tubing and filter conditions will impact protein stability without PP over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tubing set, the maximum dwell time would be up to 4 h from insulin reservoir to delivery . Previous studies in vitro have not shown fibrillation or degradation occurring at 4 h. ,,, However, it remains to be determined how exposure to tubing and filter conditions will impact protein stability without PP over time.…”
Section: Discussionmentioning
confidence: 99%
“…tubing set, the maximum dwell time would be up to 4 h from insulin reservoir to delivery. 54 Previous studies in vitro have not shown fibrillation or degradation occurring at 4 h. 32,36,63,64 However, it remains to be determined how exposure to tubing and filter conditions will impact protein stability without PP over time. Notwithstanding these conformational changes, we tested insulin activity following Z-Y filtration by infusion in chemically induced diabetic mice.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Ohno et al [34] reported a frequency dependency towards the stability of aqueous insulin solutions where, at a very low stimulation of 0.5 Hz, no loss of stability was seen, however after 24 h of constant vibration at approximately 14 Hz at 37 • C, a significant increase in the turbidity was observed. Drone delivery services are typically of a much shorter duration, but flight times to distant islands, (e.g., isolated communities in the South Pacific) that require larger drones powered by combustion engines, may generate the exposure times reported in the insulin laboratory studies described by Ohno et al [34].…”
Section: The Effects Of Vibration On Medical Cargoes During Transitmentioning
confidence: 99%
“…Specific additives can be added to the formulation to prevent bacterial growth and protein aggregation, or to modify the in vivo absorption kinetics of insulin. For example, m-cresol could be added to suppress insulin amyloid formation (Ohno et al 2019). Complexation of insulin with zinc and/or protamine can generate intermediate-or long-acting formulations (Waller and Sampson 2017).…”
Section: Formulationmentioning
confidence: 99%